The pediatric ulcerative colitis activity index (PUCAI) predicts steroid-failure in adults with acute severe colitis. (2nd September 2021) - Atia, Ohad; Gupta, Arun; Travis, Simon; Turner, Dan; Koslowsky, Benjamin
Abstract: Background: One-third of patients with acute severe ulcerative colitis (ASC) fail to respond to intravenous corticosteroids (IVCS) and require second-line therapy or colectomy. We aimed to explore the performance of the Pediatric Ulcerative Colitis Activity Index (PUCAI), for predicting response to IVCS in adults with ASC, and to base a two-step decision-making process for guiding the introduction of second-line therapy. Methods: This was a retrospective multicenter cohort study of adult patients with ASC. PUCAI score, Oxford criteria, and Swedish index were determined at baseline, day three and five of hospitalization, and discharge when outcomes were ascertained. Results: 153 patients were included (mean age 34.7 ± 14.6, median disease duration 7.8 years [IQR 0–17.4]), of whom 51 (33%) required second-line therapy, and 23 (15%) eventually underwent colectomy by discharge. At days three and five, the median PUCAI scores were higher in non-responders compared with responders (55 [45–69] vs. 38 [25–55] at day 3, and 55 [36–65] vs. 20 [5–30] at day 5; both p < .001). The negative and positive predictive values (NPV and PPV) of IVCS failure were 76/63% for the Oxford criteria, 83/52% for the Swedish index as determined on day 3, and 73/100% for PUCAI ≥ 65 points on day five. The corresponding figures for PUCAI ≥ 45 at day 3 were 83/54%. Conclusion: The PUCAI is a highly predictive tool for IVCS failure. PUCAI ≥ 45 on day 3 has an excellent NPV for IVCS failure indicating preparation for second-line therapy, and PUCAI ≥ 65 on day 5 has a high PPV to initiate the therapy.